2015
DOI: 10.1007/s11356-015-5923-3
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected effects of sublethal doses of insecticide on the peripheral olfactory response and sexual behavior in a pest insect

Abstract: Pesticides have long been used as the main solution to limit agricultural pests, but their widespread use resulted in chronic or diffuse environmental pollutions, development of insect resistances, and biodiversity reduction. The effects of low residual doses of these chemical products on organisms that affect both targeted species (crop pests) but also beneficial insects became a major concern, particularly because low doses of pesticides can induce unexpected positive--also called hermetic--effects on insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 97 publications
3
50
1
3
Order By: Relevance
“…SlitMGST1-1 and SlitMGST1-2 were indeed broadly expressed in all tissues and development stages tested whereas SlitMGST1-3 was restricted to the antenna suggesting that these three genes could have evolved different functions after a noctuid-specific duplication event. A previous study showed that SlitMGST1-3 expression is induced after deltamethrin exposure (Lalouette et al, 2016), thus suggesting a possible specialization of SlitMGST1-3 toward toxic molecules. In the beetle P. striolata two MGSTs are also preferentially expressed in the antennae of adult insects (Wu et al, 2016) meaning that members of this protein family could have conserved important function linked to olfaction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…SlitMGST1-1 and SlitMGST1-2 were indeed broadly expressed in all tissues and development stages tested whereas SlitMGST1-3 was restricted to the antenna suggesting that these three genes could have evolved different functions after a noctuid-specific duplication event. A previous study showed that SlitMGST1-3 expression is induced after deltamethrin exposure (Lalouette et al, 2016), thus suggesting a possible specialization of SlitMGST1-3 toward toxic molecules. In the beetle P. striolata two MGSTs are also preferentially expressed in the antennae of adult insects (Wu et al, 2016) meaning that members of this protein family could have conserved important function linked to olfaction.…”
Section: Discussionmentioning
confidence: 91%
“…We named all S. littoralis sequences according to the corresponding S. litura and S. frugiperda sequences (Zhang et al, 2016; Gouin et al, 2017). Subsequently the 7 S. littoralis GSTs that were previously published in (Lalouette et al, 2016), namely SlGSTe1, e2, e3, e4, d1, d2 , and d3 were respectively renamed SlitGSTe15, e8, e14, e12, d2, d3 , and SlitMGST1-3 . All sequences have been deposited in Genbank with reference accession number from MH177577 to 177613.…”
Section: Methodsmentioning
confidence: 99%
“…The regular olfactory process was also affected, since the repolarization on the antenna was reduced, while a rapid response of the olfactory receptor neurons (ORN) was induced. Thus, a faster behavioral response of males to pheromone stimulation was observed (Figure 1) [23].…”
Section: Insect Behavior As a Measurement Of Insecticide Sublethal Efmentioning
confidence: 89%
“…The results indicated that GmolGSTD1 may not be involved in the detoxification of these insecticides, which were inconsistent with the detoxification or resistance functions to insecticides of CpomGSTd2 of C. pomonella (Huang, Fan, Liu, & Feng, ), SlGSTE1 of Spodoptera litura (Xu, Zou, Zhang, Feng, & Zheng, ) and BdGSTe9 of Bactrocera dorsalis (X. P. Lu et al, ). Previous studies have shown that the insecticides can inhibit the sensitivities of insect olfactory system (Lalouette et al, ; Z. Li et al, ). For example, imidacloprid can significantly reduce the binding capacity of the odorant‐binding protein, AcerASP2, to host plant volatiles (G. Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clothianidin at a sublethal dose (0.25 ng) can significantly reduce the directional behavior of male Agrotis ipsilon to sex pheromones (Rabhi et al, ). Pyrethroid at a sublethal dose can alter the peripheral olfactory response and the courtship behavior of male Spodoptera littoralis (Lalouette et al, ). The ability of olfactory learning of the adult bees can be severely impaired after imidacloprid treatment of the larvae (K. Tan et al, ).…”
Section: Discussionmentioning
confidence: 99%